Vertically stacked PEDOT:PSS/PbS/CsPbCl3 for flexible optoelectronic devices - Zhao, Xinhong; Li, Kai; Fang, Yongchu; Tao, Yu; Song, Xiaoxian; Zhang, Haiting; Yu, Huaqing; Yan, Zaoxue (Journal of alloys and compounds, 2021)
•Vertically stacked PEDOT:PSS/PbS/CsPbCl3 photodetectors were prepared by spin-coating.•The flexible photodetectors exhibited a high responsivity and detectivity.•The performance is much higher than that of single component PbS and CsPbCl3.•The photocurrent of a series of bending had excellet stability and reproducibility. [Display omitted] Flexible photodetectors based on vertically stacked PEDOT:PSS/PbS/CsPbCl3 were prepared by a simple low temperature spin-coating method. Due to the synergistic effect, the flexible PEDOT:PSS/PbS/CsPbCl3 photodetectors exhibited a high responsivity of 6.67 A/W and detectivity of 5.78 × 1010 Jones under a relatively low external bias. The photocurrent of a series of continuous-bending shown that the flexible PEDOT:PSS/PbS/CsPbCl3 photodetectors had excellet photocurrent stability and reproducibility. The results indicate that the vertically stacked PEDOT:PSS/PbS/CsPbCl3 architecture has great potential in wearable and portable low-voltage optoelectronic devices.